2020
DOI: 10.1371/journal.pone.0236645
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of kaolin-impregnated hemostatic gauze use in preperitoneal pelvic packing for patients with pelvic fractures and hemodynamic instability: A propensity score matching analysis

Abstract: Introduction We evaluated the effectiveness of kaolin-impregnated hemostatic gauze use in preperitoneal pelvic packing (PPP) for patients with hemodynamic instability due to severe pelvic fractures. Materials and methods Between May 2014 and October 2018, 53 of 75 patients who underwent PPP due to hemodynamic instability induced by pelvic fracture were enrolled. Their medical records were prospectively collected and retrospectively analyzed. QuikClot combat gauze (hydrophilic gauze impregnated with kaolin) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Another example of hemostatic agents used is kaolin. The use of heated kaolin slurry in coating non-woven gauze is the most commonly utilized method to prepare hemostatic dressings [ 16 , 17 , 18 ]. However, this method results in low coating efficiency as can be seen in the figure ( Figure 1 A3), which explains the relatively low hemostatic efficiency of this kind of preparations (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of hemostatic agents used is kaolin. The use of heated kaolin slurry in coating non-woven gauze is the most commonly utilized method to prepare hemostatic dressings [ 16 , 17 , 18 ]. However, this method results in low coating efficiency as can be seen in the figure ( Figure 1 A3), which explains the relatively low hemostatic efficiency of this kind of preparations (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Kaolin is an inert naturally occurring hydrated aluminum silicate mineral derived from clay that is widely used as a hemostatic agent. When exposed to plasma, kaolin activates clotting factor XII, a protein factor which assists in the initiation of the coagulation cascade [ 16 , 24 ]. It was reported in one study that addition of kaolin coating materials to blood of patients on anticoagulant therapy significantly reduced the time to clot formation (in vitro testing) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the impact of PPP on SBP was evident, as shown in other series where a statistical difference was found between pre-and postoperative SBP ; they all demonstrated a statistically significant increase of SBP (12)(13)(14), as we did (p<0.001). A recent study (17) suggests that kaolin-impregnated hemostatic gauze in PPP could reduce the need for additional packed RBC transfusions in patients with hemodynamic instability due to severe pelvic fractures. This could be a useful improvement to add to reduce the transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…In various models of puncture and incision, the khadi hemostatic dressing performed relatively faster and more effectively in blood coagulation. Kaolin rapidly promotes blood coagulation by activating the factor XII protein which initiates the coagulation cascade 30,31 . In a previous study, it has been analyzed that the kaolin/chitosan composites showed significantly reduced clotting time and enhanced hemostatic efficiency 28 calculated in two rats after puncturing their leg vein and reapplying hemostatic dressing every 10 seconds until the time when the bleeding stopped.…”
Section: 11) In Vitro Hemostatic Efficiency In Ratsmentioning
confidence: 99%